An evaluation of the influence of the publication of the UK National Institute for health and Care Excellence's guidance on hypertension in pregnancy: a retrospective analysis of clinical practice - Diane Farrar; Derek Tuffnell; Trevor A. Sheldon (BMC, 2020)
Abstract Background The UK National Institute for health and Care Excellence (NICE) publish guidance aimed at standardising practice. Evidence regarding how well recommendations are implemented and what clinicians think about guidance is limited. We aimed to establish the extent to which the NICE Hypertension in pregnancy (HIP) guidance has influenced care and assess clinician's attitudes to this guidance. Methods Five maternity units in the Midlands and North of England took part in the retrospective evaluation of 2490 birth records from randomly selected dates in 2008-2010 and 2013-2015. The proportion of women where care was adhered to before (2008-2010) and after (2013-2015) guidance publication was examined and differences estimated. Eleven midwives and obstetricians employed by Bradford Hospitals were interviewed. Results The proportion of high risk women prescribed Aspirin rose (before 14%, after 54%, p = < 0.01 (confidence interval of change (CI) 37, 43%) as well as for moderate risk women (before 3%, after 54%, p = < 0.01, CI 48, 54%) following guidance publication. Three quarters had blood pressure and a third proteinuria measured at every antenatal visit before and after guidance. Early birth < 37 weeks and ≥ 37 weeks gestation was more frequently offered after guidance publication than before (< 37 weeks: before 9%, after 18%, p = 0.01, CI 2, 16% and ≥ 37 weeks before 30%, after 52%, p = < 0.01, CI 9, 35%). Few were informed of future risk of developing a hypertensive disorder or had a documented postnatal review; however there was an increase in women advised to see their GP for this review (58% before and 90% after guidance p = < 0.01, CI 24, 39%). All clinicians said the NICE HIP guidance was informative and provided robust evidence, however they said length of the document made use in practice challenging. They did not always access NICE guidance, preferring to use local guidance at least initially; both obstetricians and midwives said they accessed NICE guidance for in-depth information. Conclusions NICE HIP guidance is valued, used by clinicians and has influenced important aspects of care that may help improve outcomes for women who develop hypertension or pre-eclampsia, however some recommendations have had limited impact and therefore interventions are required to improve adherence.